Peran Kopontren dalam Meningkatkan Kompetensi Wirausaha Santri - Hakim, Muhammad Arif; Lailiyyah, Hurrotul; Widayanti, Yuyun (JIOSE: Journal of Indonesian Sharia Economics, 2023)
This study aims to identify the progress of cooperatives located in At-Taslim Islamic Boarding School, Bintoro Village, Demak District, Demak Regency. Entrepreneurial activities carried out within the framework of Kopontren, as well as the role of Kopontren At-Taslim in improving the entrepreneurial skills of students are interesting findings. This research was conducted using field research methods and using a qualitative descriptive approach. Data were collected through interviews, observations, and documentation involving informants related to the research issue. The results of this study noted that entrepreneurial activities carried out in the At-Taslim Kopontren environment include the At-Taslim Kopontren business unit in Bintoro Village, the "Mu'awanah" wood business unit in Karang Mlati Village, and the Refillable Drinking Water Depot (DAMIU QIYA) business unit in Wonosalam Village. The role of Kopontren At-Taslim in improving the entrepreneurial competence of students is able to train the entrepreneurial ability of students to be skilled and contribute both to themselves and in the entrepreneurial environment at Kopontren At-Taslim.